An optimal measurement placement method for power system harmonic state estimation - Chakphed Madtharad (2018)
This paper focuses on a new technique for optimal measurement placement for power system harmonic state estimation (HSE). The solution provides the optimal number of measurements and the best positions to place them, in order to identify the locations and magnitudes of harmonic sources. The minimum condition number of the measurement matrix is used as the criteria in conjunction with sequential elimination to solve this problem. Two different test systems are provided to validate the measurement placement algorithm. A three-phase asymmetric power system has been tested using the New Zealand test system, while the IEEE 14-bus test system has been used for testing a balanced power system. © 2005 IEEE.